How smartphone advertising influences consumers’ purchase intention - Costa, Catarina Isabel Cavaleiro (2017)
In the last decade, the use of smartphones has grown steadily. The way consumers interact with brands has changed owing to the accessibility of an internet connection on smartphones, and ubiquitous mobility. It is crucial to understand the factors that motivate consumers to interact with smartphone advertisements and therefore what stimulates their decision to purchase. To achieve this goal, we proposed a conceptual model that combines Ducoffe’s web advertising model and flow experience theory. Based on the data collected from 303 respondents, from a European country, we empirically tested the conceptual model using a partial least squares (PLS) estimation. The results showed that advertising value, flow experience, web design quality, and brand awareness explain purchase intention. The study provides results that allow marketers and advertisers to understand how smartphone advertisements contribute to consumer purchase intention.